Reducing biogenic amine in seriflux and huangjiu by recycling of seriflux inoculated with Lactobacillus plantarum JN01. (December 2021) - Liu, Shuangping; Sun, Hailong; Liu, Caixia; Zhou, Zhilei; Mao, Jieqi; Hu, Zhiming; Xu, Xibiao; Han, Xiao; Zhang, Songjing; Mao, Jian
Graphical abstract: Highlights: Putrescine and tyramine are main (>50%) BA in seriflux and huangjiu . Lactic acid bacteria occupied > 90% in seriflux microbiota. Lactobacillus plantarum JN01 inoculation reduced 78.4% of BA in recycled seriflux. BA content in huangjiu was reduced by 87.7%. No flavor impacts on huangjiu were observed by recycling seriflux. Abstract: High content of biogenic amine (BA) in huangjiu could pose serious quality concerns. More than 71% of BA in huangjiu were carried over from seriflux (rice soaking wastewater), which were produced by some BA producing bacteria during rice soaking process. A BA non-producing strain, Lactobacillus plantarum JN01, was introduced to rice soaking process, which decreased BA content in seriflux by 93.8% by niche competition at bench scale. Recycling of seriflux inoculated with L. plantarum JN01 at pilot run scale for ten batches demonstrated that BA in seriflux and huangjiu were reduced by 78.4% and 87.7%, respectively. The safety of huangjiu was enormously improved without affecting on the profiles of flavor compounds. Our results demostrated that seriflux recycling technology could reduce 50% of water consumption and achieve "zero effluents" in rice soaking process, which might potentially be a "green technology" not only for huangjiu brewing industry, but also for other related traditional fermented food industries.